Caracterización química y estabilidad aeróbica de tres variedades de cáscara de maracuyá. - Véliz Guillen, Abiut Isaías (2017)
The availability of food is an essential requirement to promote an increase in production and the sustained improvement of the agricultural sector in the coastal zone of Ecuador. In this sense, knowledge of agro-industrial by-products and their use in animal feed offer new strategies for the development of a sustainable livestock. Therefore, the research was conducted in the Laboratory of Rumiology and Nutritional Metabolism of the experimental farm "La María", of the State Technical University of Quevedo (UTEQ), and aimed to determine the chemical and fermentative composition of the shell of three varieties of passion fruit (Passiflora edulis), yellow, purple and improved (yellow x purple). The data were distributed under a Completely Randomized Design (DCA) with six repetitions and three treatments T1 CMA (Yellow passion fruit shell), T2 CMM (Purple passion fruit shell) and T3 CMAxM (yellow passion fruit shell per purple). For this purpose, favorable results were obtained in the composition: Dry matter (MS) 92.32%, ash (11%), protein (8.55%), neutral detergent fiber (FDN) 25.96%, and acid detergent fiber (FDA) (63.39 %). Variables of aerobic stability were also recorded, such as pH (5.19) and temperature (25.25). The chemical composition of the three varieties of passion fruit husks determined favorable responses to the increase of the content and nutrients with the yellow variety, and the decrease of the fiber content in the yellow variety per dwelling, being this an alternative for the feeding of ruminants.